KEDUDUKAN TANAH BENGKOK SEBAGAI HAK ASAL USUL PASCA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Dwiyana Achmad Hartanto (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2016)
The research was done because of the separate law regulating the village, namely Law No. 6 of 2014 concerning Desa (Village Law). Provisions in the Village Law requires a paradigm shift toward the village, where to place the village as a subject not related objects rural development within the framework of the Unitary Republic of Indonesia. One of the things that is being debated is related to the management of a crooked land. Prior to the enactment of Law No. 6 of 2014 on the village, the village crooked land is an asset which was partly used to provide compensation / income for the village head and the village because of his position. This right is referred to as the origin of the rights inherent for the job. With the Act the village, the village head and village get pengasilan fixed and allowances budgeted in APB village a source of funding is the revenue villages and ADD. Their fixed income and this additional polemical for the continuity of the village administration, because of the Law of the village is considered removing government authority crooked village to work the land as compensation for his position.